Using the Binary logistic regression to determine the most important economic and social factors that lead to Women's deaths during pregnancy and childbirth - A field study on the state of Khartoum – Sudan- during the year 2018 – - Babiker, Anowr Elzian; Mohamed, Mahir Fageery (Journal of Economic, Administrative and Legal Sciences, 2020)
The study was prepared to determine the most important economic and social impact on the mortality of Women during pregnancy and childbirth in Khartoum State.The study used the descriptive analytical methodology and based on preliminary data collected from a random sample of 332 Women in Khartoum state with 161 deaths and 161 lives. The study found a number of results. The factors that lead to the probability of death among Women in Khartoum state during pregnancy and childbirth (The age of marriage, the age at the time of childbirth, the age at which the first child was born, the number of rooms in the house, the type of house construction, the ownership of the house, the type of toilet used in the home, the psychological and social pressures during pregnancy), That all the models reached have significant statistical significance and have a high probability of classification, Where the overall correct classification percentage was for the main sample characteristics factors model (73.0%), the social factors model (74.0%) and the economic factors model (89%).The study concluded with a number of recommendations, the most important of which are the importance of raising the level of awareness among the different Women in the field of combating FGM / C. Women, who are considered harmful habits and factors that may lead to the death of women during pregnancy or childbirth raise the level of awareness of families in the fight against early marriage among Women with the need to develop legislation to prevent the marriage of minors, the importance of voluntary organizations and community and government agencies Mia has a role in assisting poor families who can't provide adequate health care and diet for Women during pregnancy, childbirth and after childbirth.
Keywords: logistic regression; mortality; women; pregnancy; childbirth